Tiktok Social Media Analysis of Content for Your Page with AHP (Analytical Hierarchy Process) Method - Nuning Khanif Aulia (International Journal Science and Technology, 2025)
With increasing competition in the content market, social media users are required to constantly monitor the situation and competitiveness of the market when determining their strategies as content creators. Using TikTok can help increase daily live mobilization. Effective decision-making using the AHP method can play a crucial role in determining competitive strategies, enabling content creators to determine which social media platforms to use to maintain their daily activities. This study utilized primary data through direct observation of content creators with over 10,000 followers and administered a questionnaire. In line with this issue, this study employed the Analytical Hierarchy Process (AHP) method to determine the decisions of content creators in expressing their creative ideas. The AHP model utilizes all available information to determine criteria for social media platforms, allowing for a more comprehensive and accurate analysis.